2022
DOI: 10.1101/2022.10.04.510658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neonatal mouse model characterizes transmissibility of SARS-CoV-2 variants and reveals a role for ORF8

Abstract: Small animal models have been a challenge for the study of SARS-CoV-2 transmission, with most investigators using golden hamsters or ferrets. Mice have the advantages of low cost, wide availability, less regulatory and husbandry challenges, and a versatile reagent and genetic toolbox. However, adult mice do not transmit SARS-CoV-2. Here we establish a model based on neonatal mice that allows for transmission of clinical SARS-CoV-2 isolates. We characterize tropism, respiratory tract replication and transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 177 publications
0
4
0
Order By: Relevance
“…In addition to quantifying RNA copy numbers, which can be misleading with RNA viruses, our experiments also quantify infectious viruses. While several useful animal models have been developed to study SARS-CoV-2 (14, 15) we find that our patient-derived nasal epithelia model more faithfully reflects replication kinetics in the human nose, the first site of infection.…”
Section: Introductionmentioning
confidence: 85%
“…In addition to quantifying RNA copy numbers, which can be misleading with RNA viruses, our experiments also quantify infectious viruses. While several useful animal models have been developed to study SARS-CoV-2 (14, 15) we find that our patient-derived nasal epithelia model more faithfully reflects replication kinetics in the human nose, the first site of infection.…”
Section: Introductionmentioning
confidence: 85%
“…The significance of the ORF-6 region in antagonizing interferon signalling during SARS-CoV-1 infections is well-established. However, conflicting findings exist regarding the role of ORF6 in SARS-CoV-2 infection, with studies showing both direct interference with IFN signaling through binding to nucleoprotein Nup98 and contradictory outcomes in animal models, including mice and hamsters [66][67][68][69][70] . Interestingly, there was limited diversity found in the Spike protein.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 30% of hACE2 KI C57BL/6 mice were seropositive for SARS-CoV-2 antibodies through exposure to respiratory droplets, and successful aerosol inoculation of hACE2 mice required elevated viral concentrations [114]. Rodriguez et al demonstrated that neonatal K18-hACE2 mice aged 4-7 days could release the virus and transmit it among siblings within the same litter, resulting in a 100% mortality rate among the exposed pups [115].…”
Section: Mouse Modelsmentioning
confidence: 99%